Effect of uneven heat load on the airflow uniformity and thermal performance in a small-scale data center - Jao, Yi-Chen; Zhang, Ze-Wen; Wang, Chi-Chuan (Applied thermal engineering, 2024)
•Effect of uneven heating load on the flow distribution across the data racks.•Tests are conducted for semi-enclosed, fully enclosed and non-enclosed aisle.•A higher flowrate of 3.4 CMS, mal-distribution is small for the case of uniform load.•Mal-distribution occurs for semi-enclosed cold and hot aisles at uneven load.•Severe recirculation leads to more uniform airflow distribution for non-enclosed aisle. The loading of server racks in datacenter may vary appreciably subject to the operation conditions. This can be easily seen in datacenters that are owned and run by certain internet service provider (ISP) who offers colocation to certain small companies. It is quite likely that some of the data racks are running with high load while some are running with light load or even idle. In this regard, the data racks are commonly facing uneven loading which may cause uneven airflow distribution because significantly temperature difference across the data racks. The incurred flowrate mal-distribution may overheat the data racks and cause hazard system shutdown. For better understanding these phenomena, the present study experimentally examines the airflow distribution in air-cooled data center having semi-enclosed, fully enclosed, and non-enclosed aisle configurations under varying heat loads. Note that the uneven heating load on the airflow distribution in data racks were not reported yet. The simulated data center contains 10 data racks having a total thermal power of 50 kW. For the uniform heating case, all the data racks are operated with 5 kW, and for uneven case, one side of the data racks contains 7.5 kW heat generation for each data rack and the thermal power in the other side of data racks is 2.5 kW. The tested flowrates are 2.4 CMS (cubic meter per second) and 3.4 CMS, respectively. In this study, 15 cases with different heating load, configurations, and air flowrate are investigated. It is found that for a higher suppled flowrate of 3.4 CMS, mal-distribution is rather small for the case of uniform heating load. Conversely, for both the semi-enclosed cold and hot aisles, under uneven heating load, the difference in air volumetric flowrate increases between the two sides, with higher flowrate on the side of hotter racks. In the case of fully enclosed cold aisles, the mal-distribution is rather small, while in fully enclosed hot aisles, the mal-distribution occurs due to the lower pressure within the cold aisle. In the case of non-enclosed aisle, severe heat recirculation leads to more uniform airflow distribution. However, when the supply flow rate is reduced to 2.4 CMS, significant increase in airflow mal-distribution occurs under uneven heating load conditions for all configurations, including semi-enclosed, fully enclosed, and non-enclosed aisle.